Association Between BDNF Val66Met Polymorphism and Optic Neuritis Damage in Neuromyelitis Optica Spectrum Disorder - Shen, Ting; Gupta, Vivek; Yiannikas, Con; Klistorner, Alexander; Graham, Stuart L.; You, Yuyi (Frontiers in Neuroscience, 2019)
Neuromyelitis Optica spectrum disorder (NMOSD) is an autoimmune inflammatory disease of the central nervous system (CNS). The purpose of the study was to examine the association between the brain-derived neurotrophic factor (BDNF) Val66Met genotype and structural and functional optic nerve damage in the eyes of NMOSD patients. A total of 17 NMOSD subjects (34 eyes) were included in the study and were divided into subgroups based on optic neuritis (ON) history and BDNF Val66Met polymorphisms. The mean (range) age was 47.8 (23-78) years, and the mean (SD) disease duration was 7.4 (2-39) years. All participants had undergone optical coherence tomography (OCT) scans for global retinal nerve fibre layer (gRNFL) and ganglion cell-inner plexiform layer (GCIPL) thickness and multifocal visual evoked potential (mfVEP) test for amplitude and latency. BDNF Val66Met polymorphisms were genotyped in all participants. OCT and mfVEP changes were compared between two genotype groups (Met carriers vs Val homozygotes) by using the generalised estimating equation (GEE) models. The BDNF Val66Met polymorphism was significantly associated with more severe nerve fibre layer damage and axonal loss in ON eyes of NMOSD subjects. Met carriers had more significantly reduced GCIPL (P=0.002) and gRNFL (P<0.001) thickness as well as more delayed mfVEP latency (P=0.008) in ON eyes. No association was found between Val66Met variants and NON eye of the participants. These findings suggest that the BDNF Val66Met polymorphism may be associated with optic nerve damage caused by acute optic neuritis attacks in NMOSD patients.